BURDEN OF PROOF: PROCEDURAL UNDERSTANDING OF STANDARD OF PROOF - Jurkeviča, Tatjana; Šmits, Kaspars (Administrative and Criminal Justice, 2017)
Topicality of a subject-matter “Burden of proof: Procedural understanding of standard of proof” is based on ambiguous understanding of the standard of proof in legal practice, that is, of the moment when a fact is considered to be proven or unproven. Goal of an article is to research legal regulation of burden of proof in civil procedure, administrative 51ADMINISTRATĪVĀ UN KRIMINĀLĀ JUSTĪCIJA 2017 3 (80) procedure, administrative offence procedure and criminal procedure law and to determine standard of proof within each of these procedures. Burden of proof, or duty to prove claimed fact, is an essential element of any evidentiary proceedings. Determination of standard of proof is ambiguously understood issue in legal theory and especially in legal practice. Ambiguous understanding of standard of proof in legal practice may cause determination of unproven facts as proven or vice versa, or even lead to finding innocent persons as guilty. Authors, by researching burden of proof in mentioned proceedings, provides an explanation on legal aspects of its standards.